Implementation of Project-Based Learning in Social and Human Sciences Course for First Year Students in Dentistry in Morocco - Taiebine, Mohamed; Ech-Chahdi, Amal El Ouazzani; Nejjari, Chakib (Buletin Konseling Inovatif, 2025)
The purpose of this study was to report on the experience of using Project-based learning (PBL) in the human and social sciences course taught to first year students in dentistry at the Euro-Mediterranean University of Fez. The assessment method involved self-assessment using a questionnaire. The course plan used PBL methodology in face-to-face format as well as asynchronous meetings via Moodle®. The findings showed that students were satisfied while experimenting PBL which creates a dynamic learning environment. Based on the findings, we suggest an innovative neuropsychological framework of PBL encompassing socio-cognitive, socio-emotional and metacognitive domains. Such learning enhances students' understanding of human sciences applied to dentistry, develops critical thinking skills, promotes collaboration, and prepares them for clinical practice.